2016
DOI: 10.11604/pamj.2016.24.25.7244
|View full text |Cite
|
Sign up to set email alerts
|

Sports anaemia and anthropometric evaluation of footballers at Kwame Nkrumah University of Science and Technology (KNUST)

Abstract: IntroductionSports anaemia is a physiological activity that occurs amongst footballers and may be due to poor diet, over-training, as well as an increase in plasma volume in endurance training activities. High plasma volume leads to changes in haematological parameters that may impact on endurance of footballers. The objective of the study was to determine the correlation between haematological and an-thropometric indices and their role in sports anaemia in a tropical setting.MethodsVenous blood was taken into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 27 publications
0
1
0
7
Order By: Relevance
“…The study by Opoku-Okrah et al 20 assessed anemia among futsal players and reported a reduction in hematological parameters, including hemoglobin concentration, hematocrit and red blood cell count, pointing out that such changes can lead to a condition known as “sport anemia” or “pseudoanemia”. 20 In the present study, there were a large number of athletes practicing futsal and adolescents in this modality were significantly related to the higher frequency of low hemoglobin. Thus, further studies are needed to understand and confirm or not this association.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Opoku-Okrah et al 20 assessed anemia among futsal players and reported a reduction in hematological parameters, including hemoglobin concentration, hematocrit and red blood cell count, pointing out that such changes can lead to a condition known as “sport anemia” or “pseudoanemia”. 20 In the present study, there were a large number of athletes practicing futsal and adolescents in this modality were significantly related to the higher frequency of low hemoglobin. Thus, further studies are needed to understand and confirm or not this association.…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan 8 kepustakaan yang dikaji, tiga diantaranya menjelaskan pengaruh aktivitas fisik atau latihan fisik terhadap Indeks Massa Tubuh (IMT) [11][12][13] . Dua dari tiga kepustakaan menyatakan bahwa aktivitas fisik menurunkan IMT seseorang 11,13 .…”
Section: Gambar 1 Diagram Alur Yang Menggambarkan Berbagai Tahapan Pa...unclassified
“…Empat dari delapan kepustakaan menjelaskan aktivitas fisik pada pasien anemia 12,[14][15][16] . Pada penelitian Tsai dkk didapatkan adanya korelasi antara aktivitas fisik dengan kadar hemoglobin.…”
Section: Gambar 1 Diagram Alur Yang Menggambarkan Berbagai Tahapan Pa...unclassified
See 2 more Smart Citations